Representations of children 5-6 years old about electric current: a qualitative approach - Ravanis, Konstantinos; Timpili, Dimitra; Kaliampos, George (Tauladan Fathimah Azzahra, 2023)
The present study aimed to investigate the mental representations of 5–6-year-old children about electric current. The research was qualitative in nature and was conducted using semi-directed individual interviews along three directions: An initial approach to children's mental representations regarding the presence of electric current in familiar environments, the place of its generation as well as the transport of it to houses. The findings showed that children tend to deal with the topic intuitively, mainly relying on their individual experiences. In addition, the findings revealed that despite the difficulties they face, young children have already formed some naïve mental representations about electric current. These results are part of a broader field of findings in the area of Early Childhood Education that studies the development of young children's thinking about natural phenomena and physical science concepts.